Forms of Military-Patriotic Education of Students Through Art: Results of the Formative Stage of the Research - Ragozina Victoriіa (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article deals with the forms of implementing military-patriotic education of students through art based on institutions of general secondary education and primary specialized art education, which constitutes the purpose of the study. The research objectives include: to reveal the pedagogical potential of the developed forms, to present the experience of their implementation with an emphasis on using art as an educational tool in achieving the goals of military-patriotic education. To achieve this aim, the following methods were used: theoretical methods – analysis of scientific literature related to the research problem; experimental methods – a formative experiment to check the developed forms of military-patriotic education; empirical methods – pedagogical observation and generalization of pedagogical experience to determine the effectiveness of the proposed forms and to identify prospects for their practical implementation in educational institutions. The article presents the results of the formative stage of the research conducted within the framework of the applied research project “Forms and Methods of Military-Patriotic Education of Student Youth through Art” carried out by the author at the Department of National-Patriotic Education of the Institute of Problems on Education of the National Academy of Educational Sciences of Ukraine. A number of innovative forms of military-patriotic education of students through art have been developed and tested, including: the art project “Military-Patriotic Murals”, which enabled students to explore monumental art as a tool for visualizing heroism and fostering an active civic stance; the All-Ukrainian national-patriotic online action song, which proved effective in fostering a sense of unity and promoting patriotic ideas in an accessible and dynamic format; film viewing with a creative component and discussion, which contributed to a deep emotional impact, the formation of historical awareness, and the development of students’ critical thinking skills. The research results confirmed the effectiveness of the developed forms, their relevance to contemporary educational trends, their responsiveness to students’ needs, and their suitability for integration into the educational process. The study emphasizes the necessity of uniting the efforts of educational institutions in partnership with parents and communities to create a holistic educational environment, where consistent patriotic messages and examples integrated through art significantly enhance their impact. A promising direction for educational work with students through art is highlighted: using the Ukrainian musical repertoire in events on military-patriotic themes. This opens the way to the deep formation of national identity and patriotic worldview through art.